Defect Sites in Zeolites: Origin and Healing. Issue 4 (27th November 2021) - Palčić, Ana; Moldovan, Simona; El Siblani, Hussein; Vicente, Aurelie; Valtchev, Valentin
Abstract: This paper deals with the synthesis conditions–defect formation relationship in zeolites. Silicalite‐1 (MFI‐type) is used as a model material. Samples synthesized from a system with high basicity (at 100 °C), a system with moderate basicity (at 150 °C), and a fluoride‐containing system in neutral medium (at 170 °C) are compared. Well‐crystallized materials with sizes ≈0.1, 1–10, and 30–40 µm are obtained. The samples are analyzed by complementary methods providing information on the short‐ and long‐range order in the zeolite framework. A strong correlation between the number of point defects in the zeolite framework and preparation conditions is established. Silicalite‐1 synthesized under mild synthesis conditions from a highly basic system exhibits a larger number of framework defects and thus low hydrophobicity. Further, the calcined samples are subjected to aluminum and silicon incorporation by postsynthesis treatment. The Al/Si incorporation in the zeolite framework and its impact on the physicochemical properties is studied by XRD, TEM/SEM, solid‐state NMR, FTIR, and thermogravimetric analyses. The defects healing as a function of the number of point defects in the initial material and zeolite crystal size is evaluated. The results of this study will serve for fine‐tuning zeolite properties by in situ and postsynthesis methods. Abstract : A quantitative correlation between zeolite synthesis conditions and defect formation is exemplified by studying MFI‐type materials. Postsynthesis modification with Si/Al results in Si/Al incorporation in the zeolite framework and healing point defects. The efficiency of the process in terms of the amount of healed defects with respect to their number in the parent material and zeolite crystal size is assessed.